EDITORIAL - BRAZILIAN JOURNAL OF MANAGEMENT & INNOVATION (RBGI) V. 10, n. 2, Jan/Apr, 2023 - Panizzon, Mateus (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2023)
This document introduces the articles published at the issue.